2022
DOI: 10.1111/jocs.16223
|View full text |Cite
|
Sign up to set email alerts
|

Rapid deployment technology versus conventional sutured bioprostheses in aortic valve replacement

Abstract: Objectives: Despite the benefits of rapid deployment aortic valve prostheses (RDAVR), conventional sutured valves (cAVR) are more commonly used in the treatment for aortic stenosis. Given the paucity of randomized studies, this study aimed to synthesize available data to compare both treatment options. Methods: A systematic search of Pubmed, OVID, and MEDLINE was conducted to retrieve comparative studies for RDAVR versus cAVR in the treatment of aortic stenosis. Out of 1773 returned titles, 35 papers were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
(345 reference statements)
0
10
2
Order By: Relevance
“…Thus, a decision was made to replace the aortic valve. The native aortic valve was excised, and the annulus was debrided Innovations 19 (2) from calcium and measured to fit a 19 mm bioprosthetic valve. The dissection flap in the noncoronary sinus was repaired with injecting BioGlue into the false lumen.…”
Section: Case Reportmentioning
confidence: 99%
“…Thus, a decision was made to replace the aortic valve. The native aortic valve was excised, and the annulus was debrided Innovations 19 (2) from calcium and measured to fit a 19 mm bioprosthetic valve. The dissection flap in the noncoronary sinus was repaired with injecting BioGlue into the false lumen.…”
Section: Case Reportmentioning
confidence: 99%
“… 49 Another meta-analysis demonstrated that PVL is significantly more prevalent in SRDV than SAVR using a stented bioprosthesis, and a sub-analysis by prosthetic valve type also corroborated this finding. 8 Even mild PVL can have a significant impact on survival in both conventional SAVR and TAVR, 51 , 52 highlighting the importance of careful attention to PVL in SRDV. If left untreated, PVL can lead to increased diastolic left ventricular pressure and volume overload.…”
Section: Potential Complications Of Sutureless and Rapid Deployment V...mentioning
confidence: 99%
“… 6 However, high rates of permanent pacemaker implantation (PPI) and paravalvular leakage (PVL) are two potential drawbacks of SRDV compared to SAVR using a stented bioprosthesis. 7 , 8 Despite recent cumulative experiences with SRDV have been reported recently, there is no specific recommendation for SRDV in the current guidelines, 9 , 10 and the appropriate indication for SRDV is still to be defined. This review discusses the technique of SAVR using SRDV, and specific considerations including appropriate patient selection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SU-AVR is known to be associated with a higher risk of rhythm disturbance or postoperative pacemaker implantation compared to the standard AVR. 1,[3][4][5]8,9 Finally, SU-AVR may pose an unknown risk of reoperation on a rapid deployment or sutureless bioprosthesis or the proximal aorta down the road. Although SU-AVR may facilitate minimally invasive approach such as right thoracotomy or upper hemisternotomy, 2,10 all factors mentioned above may eliminate the benefits expected in standard AVR using a stented bioprosthesis in the low-risk, young population given a longer life expectancy and the component of aortopathy in BAV patients which may develop with time.…”
Section: What Is the Role Of Su-avr Over Standard Avr In Bav Population?mentioning
confidence: 99%
“…These patients' background is different from the tricuspid AS population who are usually older and may have concomitant coronary artery and/or mitral valve diseases. In addition, SU‐AVR is known to be associated with a higher risk of rhythm disturbance or postoperative pacemaker implantation compared to the standard AVR 1,3–5,8,9 . Finally, SU‐AVR may pose an unknown risk of reoperation on a rapid deployment or sutureless bioprosthesis or the proximal aorta down the road.…”
Section: What Is the Role Of Su‐avr Over Standard Avr In Bav Population?mentioning
confidence: 99%